Spotlight: Batik Merbok indulgence / UiTM Cawangan Kedah - UiTM, Cawangan Kedah (UiTM Cawangan Kedah, 2022)
Batik Merbok is proudly designed and produced by UiTM Kedah Branch. The establishment of Batik Merbok project is as a contribution to the community especially in terms of economy, socio, culture and heritage. The designs are inspired by the elements of flora, fauna and historical remains found in the Merbok district.